Flying Parts : best practices in organisational innovation following implementation of new technologies - Kleinsmith, Niela; Koene, Bas, 1966-; Ahlstrand, Roland (London : Rotterdam School of Management, Erasmus University, 2018)
Flying Parts, a mid-sized European component parts manufacturer for the aerospace industry, implemented a range of new technologies in the early 2000's when it became a Tier 1 subcontractor. The implementation of these new technologies triggered an organisational transformation: jobs and roles were redefined, a team structure replaced a hierarchical one, selected lean principles were introduced to increase quality and productivity, and employees became directly implicated in problem-solving, decision-making and innovation. Although absent from the company prior to these innovations, union clubs were invited by employees and welcomed by management when these transformations occurred.
Originally Published In Kleinsmith, N., Koene, B., & Ahlstrand, R. (2018). Flying Parts: Best Practices in Organisational Innovation Following Implementation of New Technologies. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Personnel management; Business enterprises -- Technological innovations; Aeronautical instruments industry; Decision making